Fitness-related differences in the rate of whole-body evaporative heat loss in exercising men are heat-load dependent - Lamarche, D. T.; Notley, S. R.; Louie, J. C.; Poirier, M. P.; Kenny, G. P. (Experimental Physiology, 2018)
The effect of aerobic fitness (defined as rate of peak oxygen consumption) on heat loss during exercise is thought to be related to the level of heat stress. However, it remains unclear at what combined exercise and environmental (net) heat load threshold these fitness-related differences occur. To identify this, we assessed whole-body heat exchange (dry and evaporative) by direct calorimetry in young (22 ± 3 years) men matched for physical characteristics with low (Low-fit) (39.8 ± 2.5 mLO2·kg-1·min-1), moderate (Mod-fit) (50.9 ± 1.2 mLO2·kg-1·min-1), and high (High-fit) (62.0 ± 4.4 mLO2·kg-1·min-1) aerobic fitness (each n = 8), during three 30-min bouts of cycling in dry heat (40°C, 12% relative humidity) at increasing rates of metabolic heat production of 300 (Ex1), 400 (Ex2), 500 W (Ex3), each followed by a 15-min recovery period. Each group was exposed to a similar net heat load (metabolic plus ~100 W dry heat gain; P = 0.83) during each exercise bout (~400 (Ex1), ~500 (Ex2) and ~600 W (Ex3); P < 0.01). However, while evaporative heat loss was similar between groups during Ex1 (P = 0.33), evaporative heat loss was greater in the High-fit [Ex2: 466 ± 21 W; Ex3: 557 ± 26 W] compared to the Low-fit [Ex2: 439 ± 22 W; Ex3: 511 ± 20 W] during Ex2 and Ex3 (P = 0.03). Conversely, evaporative heat loss for the Mod-Fit did not differ from either the High-fit or Low-fit during all exercise bouts (P = 0.09). We demonstrate that aerobic fitness modulates heat loss in a heat-load dependent manner, such that young highly-fit men display greater heat-loss capacity only at heat loads ~=500 W compared to their lesser trained counterparts.